Possibility of Removing Pb and Cd from Polluted Water by Modified Fly Ash. (13th August 2021) - Chen, Xi; Zhang, Guibin; Li, Jingtian; Ji, Puhui
Abstract : In this study, fly ash (FA) was modified by sodium hydroxide to prepare a new adsorption material (IP) and treat Pb 2+ - and Cd 2+ -polluted wastewater. The effect of preparation parameters (mass ratio of FA/NaOH and modification temperature) on IP adsorption performance was investigated. The results indicated that the IP4 showed the highest adsorption capacity prepared at the FA/NaOH mass ratio of 1 : 2 and the roasting temperature of 250°C. The IP4 was characterized by SEM, EDX, XRD, and FTIR analyses. The results showed that the surface morphology and microstructure of FA were significantly changed. Furthermore, in order to study the adsorption performance of Pb 2+ and Cd 2+ on IP4, the different initial concentrations of Pb 2+ and Cd 2+, pH, and contact time were analyzed, and the results indicated that IP4 has excellent adsorption capacity for heavy metals. In addition, kinetic model results demonstrated that the adsorption behavior of Pb 2+ and Cd 2+ on IP4 was better described by a pseudo-second-order model.